Artificial Intelligence trends in education: a narrative overview - Chassignol, Maud; Khoroshavin, Aleksandr; Klimova, Alexandra; Bilyatdinova, Anna (Procedia computer science, 2018)
Digital technologies have already become an internal part of our life. They change the way we are looking for information, how we communicate with each other, even how we behave. This transformation applies to many areas, including education. The main objective of this article is to identify prospective impact of artificial technologies to the study process and to predict possible changes in educational landscape. In presented literature review we considered four categories: customized educational content, innovative teaching methods, technology enhanced assessment, communication between student and lecturer. Having reviewed publications on the subject we present here a possible picture of how the Artificial Intelligence (AI) will reshape education landscape.